Role of Soluble Innate Effector Molecules in Pulmonary Defense against Fungal Pathogens - Ordonez, Soledad R.; Veldhuizen, Edwin J. A.; van Eijk, Martin; Haagsman, Henk P. (Frontiers in Microbiology, 2017)
Fungal infections of the lung are life-threatening but rarely occur in healthy, immuno-competent individuals, indicating efficient clearance by pulmonary defense mechanisms. Upon inhalation, fungi will first encounter the airway surface liquid which contains several soluble effector molecules that form the first barrier of defence against fungal infections. These include host defence peptides, like LL-37 and defensins that can neutralize fungi by direct killing of the pathogen, and collectins, such as surfactant protein A and D, that can aggregate fungi and stimulate phagocytosis. In addition, several classes of molecules have immunomodulatory activities which can direct fungal clearance from the lung. Although there is growing evidence from in vitro studies for the antifungal activity of these molecules, it remains unclear to what extent they are important in the environment of the airway surface liquid. Ionic strength, pH and the presence of mucus can have strong detrimental effects on antifungal activity, while the potential synergistic interplay between soluble effector molecules is largely unknown. In this review, we describe the current knowledge on soluble effector molecules that contribute to antifungal activity, the importance of environmental factors and discuss the future directions required to understand the innate antifungal defence in the lung.